Female Care Givers of Children with Cerebral Palsy: Quality of Life, Knowledge and Practice Regarding Ophthalmic Evaluation – A Study from Coastal Town of Southern India - Vidya Hegde; Rashmi Jain; Anupama Bappal; Rashmi Shambu; Himani Kotian (Journal of Clinical and Diagnostic Research, 2018)
Introduction: A family centered approach to the care of children with disability is a widely accepted concept. Traditionally in India, mothers or females in family are the primary care givers. Taking care of children with special needs may have an impact on the physical and mental health of care givers and hence it needs to be investigated. Aim: To know the Quality Of Life (QOL) of female caretakers of children with Cerebral Palsy (CP). The study also assessed the knowledge of the caretakers about the need for ophthalmic evaluation of these children. Materials and Methods: Thirty six consenting female care takers were administered self-designed validated questionnaire that had 22 items. It included demographic data and items to know the awareness amongst the caretakers regarding the need for ophthalmic evaluation to know the awareness amongst the caretakers regarding the need for ophthalmic evaluation. Chisquare test was used to know the association between mean QOL score and age of care taker, educational qualification and number of children in the family. It was also used to know the association between the five domains and mean QOL score. Results: The mean age of the study group was 31.39±0.707 years. Among the care givers, 41.66% were from rural background and 75% were unemployed. The mean QOL score was 40.47. Out of 36 participants, 20 (55.6%) had a mean score < 41 (good QOL), 16 (44.4%) had a mean score > 41 (poor QOL). Chi-square test showed significant statistical association between the mean QOL score and limitation of physical activities and burden (p<0.05). Out of 36 participants, 24 were not aware about the need for eye examination of CP children. Conclusion: The QOL of female caregivers of children with disabilities is influenced by several factors. There exists poor awareness regarding the need for ophthalmic evaluation among care givers.